Production, characterization, and partial amino acid sequence of xylanase A from Schizophyllum commune. - Paice, M G (1978)
Xylanase A, one of several extracellular xylanases produced by Schizophyllum commune strain Delmar when grown in submerged culture with spruce sawdust as carbon source, was purified 43-fold in 25% yield with respect to total xylanase activity. Although some polysaccharide was strongly bound to the purified enzyme, the complex could be dissociated by sodium dodecyl sulfate and appeared homogeneous on sodium dodecyl sulfate-polyacrylamide gel electrophoresis. The molecular weight of the protein, calculated from the electrophoretic mobility, was 33,000. The molecular activity of the purified xylanase A, determined with soluble larch xylan as substrate, was 1.4 X 10(5) min-1, with xylobiose and xylose as the major products. The enzyme had a pH optimum of 5.0 and a temperature optimum of 55 degrees C in 10-min assays. The acid hydrolysate of xylanase A was rich in aspartic acid and aromatic amino acids. The sequence of 27 residues at the amino terminus showed no homology with known sequences of other proteins.